Negotiating Identity in Historiographic Metafiction: The Case of Margret Atwood’s Alias Grace (1996) - Chounaa, Rania; Mouissa, Fattoum (University of Ammar Theledji -Laghouat, 2020)
Historiographic metafiction is a postmodern genre that holds the features of postmodernism such as intertextuality, parody and pastiche. It does not only hold the features of postmodernism but also embraces its themes; among these themes is identity. In this context, Identity is one of the predominant and recurrent themes in postmodern writings. The Canadian novelist Margret Atwood dedicated her writings to postulate a satisfactory concept of identity. Atwood in her novel Alias Grace (1996) interrogates how both personal and social prompts could mold one’s identity. It is eminent to consider that identity construction is an essential endeavor that the individual seeks to clarify along the process of understating the self. Following this line of thought, this dissertation attempts to explore the quest for identity construction as it examines how an individual can be the product of what was experienced in combination of the social repertoires that establish one’s identity. The main interrogation raised is how the protagonist’s identity was constructed. In fact, the main character, Grace Marks, manages to have an identity that is an amalgamation of all the experiences she went through. In other words, her identity can be read via the patchwork that she stiches by the end of the story as she uses the clothes' shreds of the most influential figures in her life such as Nancy Montgomery and her friend Mary Whitney in order to express the extent to which her past shaped her current identity